Metal injection molding aluminum-containing stainless steel material and preparation process

Through aerosol powder making and pelletizing processes, combined with oxalic acid degreasing and hydrogen thermal degreasing, and finally argon sintering and heat treatment, the problem of Al element precipitation or volatility in metal injection molding process is solved, and a high-density, high-strength aluminum-containing stainless steel material is prepared, which improves the mechanical properties and corrosion resistance of the material.

CN119824334APending Publication Date: 2025-04-15HANGZHOU SINO-MIM TECH CO LTD

Patent Information

Application Number
CN202510107683.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

It is difficult for the metal injection molding process to effectively utilize highly active material components, especially aluminum-containing stainless steel materials, which leads to the precipitation or volatility of Al elements and affects the performance of the material.

Method used

The aerosol powdering process is used to obtain low-carbon, low-oxygen and high-flow spherical metal powder, and through dense granulation and injection molding processes, combined with oxalic acid degreasing and hydrogen thermal degreasing, and finally argon sintering and heat treatment is carried out to prepare a high-density and high-strength aluminum-containing stainless steel material.

Benefits of technology

The preparation of aluminum-containing stainless steel materials with low carbon, low oxygen, high density, high strength, high corrosion resistance, high temperature creep resistance has been achieved, and the mechanical properties and corrosion resistance of the materials have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824334A_ABST
    Figure CN119824334A_ABST
Patent Text Reader

Abstract

The invention relates to the field of powder injection molding materials, in particular to a metal injection molding aluminum-containing stainless steel material and a preparation technology, and the stainless steel material comprises the following components in percentage by mass: 6-8 wt% of Ni, 15-18 wt% of Cr, 0.5-2.5 wt% of Al and 1t of C; 0.2 wt%, and the O content is lt; the low-carbon and low-oxygen metal powder is obtained through vacuum gas atomization, the metal powder is formed through the injection molding process and then is degreased through organic oxalic acid, hydrogen is adopted in the whole process of the thermal degreasing stage, and the low-carbon and low-oxygen metal powder is obtained through the gas atomization powder preparation process, so that the low-carbon and low-oxygen metal powder is obtained. The aluminum-containing stainless steel material which is low in carbon, low in oxygen, high in compactness, high in strength, high in corrosion resistance and high in high-temperature creep resistance is obtained through the processes of heat treatment, rapid heating and heat preservation, and the C content of the stainless steel material prepared through the preparation process is 1t after heat treatment; 0.2 wt%, oxygen content lt; the 0.2 wt% structure is compact, the sintering density is high, and the normal-temperature and high-temperature mechanical strength is higher than that of conventional materials such as 304L, 316L and 17-4PH.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of powder injection molding materials, and in particular to a metal injection molding aluminum-containing stainless steel material and a preparation process. Background Art

[0002] Metal injection molding (MIM) is a new net-forming processing technology for parts that introduces plastic injection molding technology into the field of powder metallurgy. It is a process in which metal powder and organic binder are mixed and extruded into granules to form feedstock, which is then injected into the molded blank, which is then degreased and sintered to become the desired finished product. This process is a net-size molding process, and has many advantages, such as high material utilization, direct molding into complex shapes, high batch production efficiency, and high dimensional accuracy, which can achieve less or even no processing of the product.

[0003] Although the metal injection molding process has many advantages, it is a powder metallurgy process and contains a lot of high molecular weight organic matter that needs to be removed in the catalytic degreasing and thermal defingering stages. Therefore, not all materials are suitable for metal injection molding production. Some materials with high activity, high sintering volatility, low sintering temperature, and carbon and oxygen sensitivity are usually not suitable for metal injection molding production.

[0004] The role of Al in nickel-containing stainless steel is mainly to form Ni3Al and NiAl precipitation phases in the martensite phase during aging, thereby achieving the purpose of strengthening. After adding Al to precipitation-hardening stainless steel, it has better resistance to uniform corrosion, intergranular corrosion and friction corrosion than precipitation-hardening stainless steels such as 17-4PH. When Al is added to stainless steel, it can improve the steel's high-temperature oxidation resistance, oxidation corrosion resistance, H2S gas corrosion and high-temperature fatigue strength.

[0005] Al addition has so many advantages in improving material properties. In traditional powder metallurgy pressing, a small amount of Al is occasionally added to improve the comprehensive performance of the material. This is because the density of traditional powder metallurgy sintering is relatively low, and there are a large number of holes inside, so Al is not easy to precipitate, and some processes take further hot pressing, rolling and other methods after sintering to improve the density and performance. For example, Chinese invention patent CN103602902A discloses a powder metallurgy pressure-resistant composite metal material and its preparation method, which contains: 316 stainless steel powder 45-47, iron powder 50-54, graphite fiber 1-2, molybdenum disulfide 1-2, aluminum 7-8.5, vanadium 4.5-5.5, molybdenum 11-13, chromium 4-5, and additives 2-3. The powder is mixed, pressed, calcined, crushed, pressed again, and sintered to become a sleeve product. The sintering temperature is only 1050-1150℃, and the density is low. Of course, the density requirements of this type of bearing and sleeve products are not high, and some micropores are retained in the sintered parts to facilitate the storage of lubricating oil and reduce friction. However, the addition of Al to metal alloy materials for metal injection molding has not been seen to improve high-temperature mechanical strength, corrosion resistance, and fatigue strength. The main reason is that Al has a low melting point, which is very different from the melting points of other elements in stainless steel such as Fe, Cr, and Ni. Conventional processes are prone to cause Al elements to precipitate or volatilize; and Al is highly active. During the metal injection molding process, it is easy to combine with C and O to form a stable aluminum carbide phase or oxide phase, which not only fails to enhance the performance of the material, but also leads to a high carbon content in the material, affecting the corrosion resistance and sintering density of the material. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide a metal injection molding aluminum-containing stainless steel material and a preparation process to solve the problem that the aluminum-containing stainless steel material cannot be produced by the metal injection molding process.

[0007] Based on the above purpose, one aspect of the present invention provides a metal injection molding aluminum-containing stainless steel material, the mass ratio of each component is: Ni content 6-8wt%, Cr content 15-18wt%, Al content 0.5-2.5wt%, C content <0.2wt%, O content <0.2wt%, Fe content 70~80wt%.

[0008] Another aspect of the present invention provides a process for preparing a stainless steel material containing aluminum by metal injection molding, comprising the following steps:

[0009] Powder making: After the raw materials are mixed according to the mass ratio, the gas atomization powder making process is used to obtain low-carbon, low-oxygen, high-flow spherical metal powder.

[0010] Mixing granulation: Spherical metal powder and high molecular organic matter are added into the mixing tank at a mass ratio of 100:8-12. The mixing tank temperature is 180-185℃ and the speed is 15r / min for 1.5h. Mix well and then extrude and granulate.

[0011] Injection molding: The granulated material was injection molded using an injection process, and the sample molding temperature was 200°C;

[0012] Catalytic degreasing: The sample was degreased in an oxalic acid degreasing furnace at a temperature of 140°C for 12 hours.

[0013] Sintering: The sample is first heated to 600-800℃ in a hydrogen atmosphere for thermal debinding, and then switched to argon atmosphere for sintering;

[0014] Heat treatment: After sintering, the sample is quenched and aged to obtain the final product.

[0015] Optionally, the spherical metal powder has a C content of <0.1 wt%, and an O content of <0.1 wt%.

[0016] Optionally, in the mixing and granulation, the high molecular organic matter is a plastic machine system mainly composed of polyformaldehyde, with a proportion of polyformaldehyde accounting for 75-90%, olefin polymer skeleton agent accounting for 5-15%, surfactants such as stearic acid and salts accounting for 1-5%, and antioxidant accounting for 1-2%, wherein the olefin polymer skeleton agent is a combination of one or more of PP, PE, PS, and EVA.

[0017] Furthermore, in the sintering process, the material is heated to 600-700°C in a hydrogen atmosphere for 4 hours, kept warm for 4-6 hours, heated to 1350-1380°C in an argon atmosphere for 4-8 hours, with a sintering partial pressure of 10-40 kPa, kept warm for 2-4 hours, and then cooled.

[0018] Optionally, the quenching temperature is 760-780° C., and the holding time is 2 hours; the aging temperature is 510-550° C., and the holding time is 4 hours.

[0019] Beneficial effects of the invention: The invention proposes a metal injection molding aluminum-containing stainless steel material and a preparation process, wherein a low-carbon and low-oxygen metal powder is obtained by a vacuum gas atomization method, the metal powder is molded by an injection molding process, and then degreased by an organic oxalic acid with weak oxidizing property, hydrogen is used throughout the thermal degreasing stage, and a rapid heating and heat preservation process is used to obtain an aluminum-containing stainless steel material with low carbon, low oxygen, high density, high strength, high corrosion resistance, and high temperature creep resistance. The stainless steel material obtained by the preparation process has a C content of <0.2wt%, an oxygen content of <0.2wt% after heat treatment, a dense structure, a sintered density of >7.60g / cm3, and higher strength values ​​in room temperature and high temperature mechanical tests than conventional materials such as 304L, 316L, and 17-4PH. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 This is a microscopic cross-sectional view of Example 2 after sintering at a magnification of 100 times;

[0022] Figure 2 This is a microscopic cross-sectional view of comparative example 3 after sintering magnified 100 times;

[0023] Figure 3 This is a metallographic image of Example 1 after sintering magnified 500 times;

[0024] Figure 4 This is a metallographic image of Example 1 after heat treatment, magnified 500 times. DETAILED DESCRIPTION

[0025] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0026] Embodiment 1:

[0027] A preparation process of aluminum-containing stainless steel material by metal injection molding, comprising the following steps:

[0028] Powder making: The raw material ratio is 6.5wt% Ni, 17.0wt% Cr, and 1.5wt% Al. A gas atomization powder making process is used to obtain high-flow spherical metal powder. The gas atomization powder making process is: raw material preparation - ratio - induction melting - spray powder making - collection and screening - batching, C content <0.1wt%, O content <0.1wt%;

[0029] Mixing and granulation: metal powder and high molecular organic matter are added into the mixing tank at a ratio of 100:9, the mixing tank temperature is 180-185℃, the speed is 15r / min, and the mixing is carried out for 1.5h. The mixture is evenly mixed and then extruded for granulation. The high molecular organic matter is 78% polyoxymethylene, 15% olefin polymer skeleton agents such as PP, PE, PS, EVA, 5% surfactants such as stearic acid and salts, and 2% antioxidants.

[0030] Injection molding: The injection molding temperature is 200°C. This injection process is a conventional injection process and will not be described in detail here.

[0031] Catalytic degreasing: Use oxalic acid degreasing furnace for degreasing, degreasing temperature is 140℃, degreasing time is 12h.

[0032] Sintering: Heat to 600℃ in hydrogen atmosphere for 4h, keep warm for 6h for thermal debinding, then switch to argon sintering, heat to 1350℃ in 4h, sintering partial pressure 20kPa, keep warm for 4h, then cool down. Figure 1 This is a metallographic image of the product after sintering, magnified 500 times.

[0033] Heat treatment: After sintering, the sample was subjected to solution treatment and aging treatment to obtain the final product. The quenching temperature was 760℃ and the holding time was 2h; the aging temperature was 520℃ and the holding time was 4h. Figure 2 This is a metallographic image magnified 500 times after heat treatment.

[0034] Embodiment 2:

[0035] Powder making: The raw material ratio is Ni content 7.5wt%, Cr content 17.0wt%, Al content 2.2wt%, and a gas atomization powder making process is used to obtain high-flow spherical metal powder, with C content <0.1wt% and O content <0.1wt%.

[0036] Mixing granulation: metal powder and high molecular organic matter are added into the mixing tank at a ratio of 100:10. The temperature of the mixing tank is 180-185°C and the speed is 15r / min for 1.5 hours. Mix them evenly and then extrude them into granules. The high molecular organic matter is 88% polyoxymethylene, 8% olefin polymer skeleton agents such as PP, PE, PS, EVA, 3% surfactants such as stearic acid and salts, and 1% antioxidants.

[0037] Injection molding: Injection molding temperature 200℃.

[0038] Catalytic degreasing: Use oxalic acid degreasing furnace for degreasing, degreasing temperature is 140℃, degreasing time is 12h.

[0039] Sintering: heat up to 650℃ in hydrogen atmosphere for 4h, keep warm for 4h, then switch to argon sintering, heat up to 1380℃ in 6h, sintering partial pressure 10kPa, keep warm for 2h, then cool down.

[0040] Heat treatment: After sintering, the sample is subjected to solution treatment and aging treatment to obtain the final product. The quenching temperature is 770℃, and the holding time is 2h; the aging temperature is 550℃, and the holding time is 4h. The microscopic cross-section after sintering is as follows Figure 1 shown.

[0041] Embodiment 3:

[0042] Powder making: The raw material ratio is Ni content 7.0wt%, Cr content 15.0wt%, Al content 1.0wt%, and a gas atomization powder making process is used to obtain high-flow spherical metal powder, with C content <0.1wt% and O content <0.1wt%.

[0043] Internal mixing granulation: metal powder and high molecular organic matter are added into the internal mixing tank at a ratio of 100:12. The temperature of the internal mixing tank is 180-185℃, and the speed is 15r / min for internal mixing for 1.5h. Mix them evenly and then extrude them into granules. The high molecular organic matter is polyoxymethylene accounting for 90%, skeleton agents such as PP, PE, PS accounting for 7%, surfactants such as stearic acid and salts accounting for 2%, and antioxidants accounting for 1%.

[0044] Injection molding: Injection molding temperature 200℃.

[0045] Catalytic degreasing: Use oxalic acid degreasing furnace for degreasing, degreasing temperature is 140℃, degreasing time is 12h.

[0046] Sintering: In hydrogen atmosphere, the temperature was raised to 700°C for 4 hours and kept at this temperature for 4 hours. Then, the temperature was switched to argon atmosphere, the temperature was raised to 1360°C for 8 hours, the sintering partial pressure was 30 kPa, the temperature was kept at this temperature for 3 hours, and then the temperature was lowered.

[0047] Heat treatment: After sintering, the sample is subjected to solution treatment and aging treatment to obtain the final product. The quenching temperature is 780℃, and the holding time is 2h; the aging temperature is 525℃, and the holding time is 4h.

[0048] Embodiment 4:

[0049] Powder making: The raw material ratio is Ni content 6.0wt%, Cr content 18.0wt%, Al content 0.5wt%, and a gas atomization powder making process is used to obtain high-flow spherical metal powder, with C content <0.1wt% and O content <0.1wt%.

[0050] Internal mixing granulation: metal powder and high molecular organic matter are added into the internal mixing tank at a ratio of 100:12. The temperature of the internal mixing tank is 180-185℃, and the speed is 15r / min for internal mixing for 1.5h. Mix them evenly and then extrude them into granules. The high molecular organic matter is polyoxymethylene accounting for 90%, skeleton agents such as PP, PE, PS accounting for 5%, surfactants such as stearic acid and salts accounting for 3.5%, and antioxidants accounting for 1.5%.

[0051] Injection molding: Injection molding temperature 200℃.

[0052] Catalytic degreasing: Use oxalic acid degreasing furnace for degreasing, degreasing temperature is 140℃, degreasing time is 12h.

[0053] Sintering: In hydrogen atmosphere, heat to 800℃ for 4h, keep at this temperature for 4h. Then switch to argon atmosphere for sintering, heat to 1350℃ for 4h, sintering partial pressure 40kPa, keep at this temperature for 4h, and then cool down.

[0054] Heat treatment: After sintering, the sample was subjected to solution treatment and aging treatment to obtain the final product. The quenching temperature was 770℃, and the holding time was 2h; the aging temperature was 515℃, and the holding time was 4h.

[0055] Comparative Example 1:

[0056] Powder making: The raw material ratio is Ni content 6.5wt%, Cr content 17.0wt%, Al content 1.5wt%. The gas atomization powder making process is used to obtain high-flow spherical metal powder. The C and O contents of the powder are measured, and the C content is <0.1wt% and the O content is <0.1wt%.

[0057] Mixing granulation: Add a certain amount of organic matter to the metal powder in proportion and put it into the mixing tank. The temperature of the mixing tank is 180-185℃, the speed is 15r / min, and the mixing is carried out for 1.5 hours. Mix evenly and then extrude and granulate.

[0058] Injection molding: Injection molding temperature 200℃, conventional injection process.

[0059] Catalytic degreasing: Use oxalic acid degreasing furnace for degreasing, degreasing temperature is 140℃, degreasing time is 12h.

[0060] Sintering: Argon gas thermal defining and sintering throughout the process. During the thermal defining stage, the temperature is raised to 600°C for 4 hours, kept at this temperature for 6 hours, and then raised to 1350°C for 4 hours after the thermal defining, with a sintering partial pressure of 20 kPa, kept at this temperature for 4 hours, and then cooled down.

[0061] Heat treatment: After sintering, the sample was subjected to solution treatment and aging treatment to obtain the final product. The quenching temperature was 770℃, and the holding time was 2h; the aging temperature was 525℃, and the holding time was 4h.

[0062] Comparative Example 2:

[0063] Powder making: The raw material ratio is Ni content 7.5wt%, Cr content 17.0wt%, and does not contain Al element. The gas atomization powder making process is used to obtain high-flow spherical metal powder. The C and O contents of the powder are measured, and the C content is <0.1wt%, and the O content is <0.1wt%.

[0064] Mixing granulation: Add a certain amount of organic matter to the metal powder in proportion and put it into the mixing tank. The temperature of the mixing tank is 180-185℃, the speed is 15r / min, and the mixing is carried out for 1.5 hours. Mix evenly and then extrude and granulate.

[0065] Injection molding: Injection molding temperature 200℃, conventional injection process.

[0066] Catalytic degreasing: Use oxalic acid degreasing furnace for degreasing, degreasing temperature is 140℃, degreasing time is 12h.

[0067] Sintering: In hydrogen atmosphere, the temperature was raised to 600°C for 4 hours and kept at this temperature for 4 hours. Then, the temperature was switched to argon atmosphere for sintering, the temperature was raised to 1350°C for 6 hours, the sintering partial pressure was 40 kPa, the temperature was kept at this temperature for 4 hours, and then the temperature was lowered.

[0068] Heat treatment: After sintering, the sample was subjected to solution treatment and aging treatment to obtain the final product. The quenching temperature was 770℃, and the holding time was 2h; the aging temperature was 525℃, and the holding time was 4h.

[0069] Comparative Example 3:

[0070] Powder making: The raw material ratio is Ni content 7.5wt%, Cr content 17.0wt%, Al content 2.2wt%, and a gas atomization powder making process is adopted to obtain high-flow spherical metal powder. The C and O contents of the powder are measured, and the C content is <0.1wt%, and the O content is <0.1wt%.

[0071] Mixing granulation: Add a certain amount of organic matter to the metal powder in proportion and put it into the mixing tank. The temperature of the mixing tank is 180-185℃, the speed is 15r / min, and the mixing is carried out for 1.5 hours. Mix evenly and then extrude and granulate.

[0072] Injection molding: Injection molding temperature 200℃, conventional injection process.

[0073] Catalytic degreasing: Use oxalic acid degreasing furnace for degreasing, degreasing temperature is 140℃, degreasing time is 12h.

[0074] Sintering: In hydrogen atmosphere, the temperature was raised to 600°C for 4 hours and kept at this temperature for 4 hours. Then, the temperature was switched to argon atmosphere for sintering, the temperature was raised to 1350°C for 6 hours, the sintering partial pressure was 60 kPa, the temperature was kept at this temperature for 4 hours, and then the temperature was lowered.

[0075] Heat treatment: After sintering, the sample is subjected to solution treatment and aging treatment to obtain the final product. The quenching temperature is 770℃, and the holding time is 2h; the aging temperature is 550℃, and the holding time is 4h. The microscopic cross-section after sintering is as follows Figure 2 shown.

[0076] The stainless steel materials produced in the above embodiments and comparative examples were tested for material properties after sintering and heat treatment. The material properties are shown in Table 1.

[0077] Table 1

[0078]

[0079] Example results:

[0080] It can be seen from the table that the aluminum-containing stainless steel material prepared by the present invention has good mechanical properties, density, hardness and low carbon and oxygen content after heat treatment, and is also very resistant to salt spray corrosion. It is a type of material with very high practicality and expands the application range of metal injection molding materials.

[0081] The high C content in Comparative Example 1 leads to poor density, mechanical properties, and salt spray corrosion resistance. The material in Comparative Example 2 does not add Al elements, and without the addition of key Al elements, Ni3Al and NiAl precipitation phases cannot be formed inside the material. Heat treatment does not have any effect on improving material performance, and the material strength and hardness are very low. Due to the deviation of the process, the Al element precipitates during sintering in Comparative Example 3 (comparison chart), resulting in low density and mechanical properties, high C / O content, and reduced corrosion resistance.

[0082] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention (including the claims) is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0083] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A metal injection molded aluminum-containing stainless steel material, characterized in that: The components of the stainless steel material are as follows by mass ratio: Ni content 6-8wt%, Cr content 15-18wt%, Al content 0.5-2.5wt%, C content <0.2wt%, O content <0.2wt%, Fe content 70-80wt%.

2. A process for preparing aluminum-containing stainless steel material by metal injection molding as claimed in claim 1, characterized in that: The steps include: Powder making: After the raw materials are mixed according to the mass ratio, the gas atomization powder making process is used to obtain high-flow spherical metal powder; Mixing granulation: Spherical metal powder and high molecular organic matter are added into the mixing tank at a mass ratio of 100:8-12. The mixing tank temperature is 180-185℃ and the speed is 15r / min for 1.5h. Mix well and then extrude and granulate. Injection molding: The granulated material is injected into a blank by injection molding process, and the injection molding temperature is 200°C; Catalytic degreasing: The sample was degreased in an oxalic acid degreasing furnace at a temperature of 140°C for 12 hours. Sintering: The sample is first heated to 600-800℃ in a hydrogen atmosphere for thermal debinding, and then switched to argon atmosphere for sintering; Heat treatment: After sintering, the sample is quenched and aged to obtain the final product.

3. The preparation process according to claim 2, characterized in that: The spherical metal powder has a C content of less than 0.1 wt % and an O content of less than 0.1 wt %.

4. The preparation process according to claim 2, characterized in that: In the mixing and granulation, the high molecular organic matter is a plastic-based system mainly composed of polyformaldehyde, with a proportion of 75-90% polyformaldehyde, 5-15% olefin polymer skeleton agent, 1-5% surfactants such as stearic acid and salts, and 1-2% antioxidants, wherein the olefin polymer skeleton agent is a combination of one or more of PP, PE, PS, and EVA.

5. The preparation process according to claim 2, characterized in that: In the sintering process, the material is heated to 600-700°C in a hydrogen atmosphere for 4 hours, kept warm for 4-6 hours, and heated to 1350-1380°C in an argon atmosphere for 4-8 hours, with a sintering partial pressure of 10-40 kPa, kept warm for 2-4 hours, and then cooled.

6. The preparation process according to claim 2, characterized in that: The quenching temperature is 760-780°C, and the holding time is 2h; the aging temperature is 510-550°C, and the holding time is 4h.

Citation Information

Patent Citations

  • Powder metallurgy pressure-resistant composite metal material and preparation method thereof

    CN103602902A

Cited By

  • Titanium-based spherical alloy and manufacturing process thereof

    CN122583565A